2006
DOI: 10.1071/rdv18n2ab188
|View full text |Cite
|
Sign up to set email alerts
|

188 Effect of Transfer of Frozen-Thawed Ivf Embryos on Pregnancy in Repeat-Breeder Inseminated or Non-Inseminated Holstein Cattle

Abstract: Repeat-breeding is one of the important factors that affect dairy management. The objective of this study was to investigate the effect of transfer of frozen–thawed IVF embryos on pregnancy in repeat-breeder Holstein cattle. Cumulus–oocyte complexes (COCs) were collected by aspiration of 2–1-mm follicles from ovaries obtained at a local abattoir. COCs were matured for 20 h in TCM-199 supplemented with 5% calf serum (CS) and 0.02 mg/mL of FSH at 38.5°C under a 5% CO2 atmosphere in air. Matured oocytes were inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In addition, the pregnancy rate following TET in the present study was similar to that (48.9%) following ET in repeat breeder dairy cattle using frozen-thawed embryos collected from Japanese black cows [19]. Moreover, Dochi et al [18] demonstrated that ET using frozen-thawed in cows received TAI 30 h (Day 9) after the second EB injection in the CIDR-based TAI protocol. TET 3 : cows received TET using frozen-thawed blastocysts or morula embryos on Day 16 in the CIDR-based TET protocol.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, the pregnancy rate following TET in the present study was similar to that (48.9%) following ET in repeat breeder dairy cattle using frozen-thawed embryos collected from Japanese black cows [19]. Moreover, Dochi et al [18] demonstrated that ET using frozen-thawed in cows received TAI 30 h (Day 9) after the second EB injection in the CIDR-based TAI protocol. TET 3 : cows received TET using frozen-thawed blastocysts or morula embryos on Day 16 in the CIDR-based TET protocol.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, embryo transfer (ET) can increase the probability of maintenance of pregnancy in lactating dairy cows by minimizing the negative effects of high milk production and heat stress on both the quality of the oocyte and early development of the embryo [17]. Similarly, this ET technique has been introduced as an efficient tool to improve fertility for repeat breeder dairy cattle [18,19]. It has also been reported that a progesterone (P4)-based timed ET (TET) protocol enables more recipients to be selected without a decrease in pregnancy rate compared with synchronization of estrus using PGF 2α [20].…”
mentioning
confidence: 99%